Game audio programming 2 : principles and practices - Somberg, Guy, ....- (Boca Raton : CRS Press, Taylor & Francis Group, an informa business, 2019)
Welcome to the second volume of Game Audio Programming: Principles and Practices – the first series of its kind dedicated to the art of game audio programming! This volume features more than 20 chapters containing advanced techniques from some of the top game audio programmers and sound designers in the industry. This book continues the tradition of collecting more knowledge and wisdom about game audio programming than any other volume in history.
Keywords: Programming